Does foreign aid harm political institutions? - Sam Jones; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The notion that foreign aid harms the institutions of recipient governments remains prevalent. We combine new disaggregated aid data and various metrics of political institutions to re-examine this relationship. Long-run cross-section and alternative dynamic panel estimators show a small positive net effect of total aid on political institutions. Distinguishing between types of aid according to their frequency domain and stated objectives, we find this aggregate net effect is driven primarily by the positive contribution of more stable inflows of 'governance aid'. We conclude the data do not support the view that aid has had a systematic negative effect on political institutions.
Keywords: F35; O17; O19; 330; foreign aid; governance; institutions; government quality